Fruta del Norte paste plant – case study - Correia, LDC; Brown, RE; Moore, D (Paste 2023: 25th International Conference on Paste, Thickened and Filtered Tailings, 2023)
Lundin Gold’s Fruta del Norte project, which is currently the largest gold deposit in Ecuador, achieved commercial production in February 2020. The project includes a mine plan that incorporates both bulk and selective mining methods. Most areas mined will use conventional transverse stoping and will be supported by the drift-and-fill mining method in zones of smaller dimension or with poor geotechnical quality. Backfill is used as a ground support medium with the majority of voids to be filled using cemented paste fill. A paste plant, used to supply the required backfill tonnage, has been constructed directly over the orebody. The design of the paste plant is unique, accounting for challenges in topography, a sensitive local environment and challenging feed tailings. The paste plant was successfully commissioned in quarter three 2020. In this case study, the design is described in how it caters for the unique requirements of the project. Further to this, construction and commissioning challenges faced and lessons learned are documented.
Keywords: paste; plant design; commissioning; construction